Świadoma intonacja i swobodne zadęcie jako metoda kształtowania pięknego dźwięku saksofonu = Beautiful saxophone sound achieved through conscious intonation and free blowing - Baron, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article addresses the rarely raised subject of applying new methods of enriching the instrument`s tone with overtones. The author discusses practical exercises that may help achieve the above-mentioned enrichment, and indicates the methodology used for working on expanding the resource and improving the quality of articulatory effects that are already in use.
Keywords: saxophone articulation; harmonization; intonation; jazz; overtones; sound